Edaphic factors and their impact on the dominant height of Prosopis alba plantations - Senilliani, María Gracia; Bruno, Cecilia; Brassiolo, Miguel (Instituto de Ecología, A.C., 2020)
Prosopis alba is the most important native species in the semi-arid Chaco for afforestation with multiple objectives. More than 50% of the planted area in Santiago del Estero, Argentina, has been established in areas with very different site quality, generating a heterogeneous growth behavior. It is proposed to evaluate the influence of edaphic factors on the growth of plantations Prosopis alba Griseb (algarrobo) in areas of the semi-arid Chaco, information that will facilitate silvicultural decision making and will allow predicting the quality of sites with forestation potential based on conditions of the soil. The correlation between dasometric and edaphic variables was evaluated in relation to 3 kinds of site quality (CI, CII and CIII). A dominant height projection model expressed as a Site Index with the most correlated edaphic variables was determined, which explains 42% of the variation in growth. The electrical conductivity has a threshold of 10 dS m-1 for the CI and CII with Site Index of 10 and 8 respectively; for higher EC values ​​the growth of the mass decreases. The concentration of soluble cations varies in relation to the site index, the CI and CII have low sodium concentrations, with a critical value of approximately 39 mEq L-1. Growth is conditioned by chemical properties of the soil, the presence of salts would further explain the impact on growth, with a saline threshold from which growth is compromised from a productive approach.